2013
DOI: 10.1051/0004-6361/201322466
|View full text |Cite
|
Sign up to set email alerts
|

Silicon isotopic abundance toward evolved stars and its application for presolar grains

Abstract: Aims. Galactic chemical evolution (GCE) is important for understanding the composition of the present-day interstellar medium (ISM) and of our solar system. In this paper, we aim to track the GCE by using the 29 Si/ 30 Si ratios in evolved stars and tentatively relate this to presolar grain composition. Methods. We used the APEX telescope to detect thermal SiO isotopologue emission toward four oxygen-rich M-type stars. Together with the data retrieved from the Herschel science archive and from the literature, … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 42 publications
2
8
0
Order By: Relevance
“…The solar 29 Si abundance is ≈ 1.4 times larger than the solar 30 Si abundance, in concordance with observations of some individual stars (Peng et al 2013) and pre-solar silicon-carbide grains (e.g., Hoppe et al 2010), yet in tension with common models of 1D core-collapse supernova, Type Ia supernovae, and AGB stars (e.g., Timmes & Clayton 1996;Lugaro et al 1999;Lewis et al 2013;Wasserburg et al 2015). It is curious that the 30 Si abundance, normalized to solar in in Figure 25, is larger than the 29 Si abundance in the M ZAMS = 20 and 30 M models but traditionally smaller in the M ZAMS = 15 and 25 M models.…”
Section: +002supporting
confidence: 90%
“…The solar 29 Si abundance is ≈ 1.4 times larger than the solar 30 Si abundance, in concordance with observations of some individual stars (Peng et al 2013) and pre-solar silicon-carbide grains (e.g., Hoppe et al 2010), yet in tension with common models of 1D core-collapse supernova, Type Ia supernovae, and AGB stars (e.g., Timmes & Clayton 1996;Lugaro et al 1999;Lewis et al 2013;Wasserburg et al 2015). It is curious that the 30 Si abundance, normalized to solar in in Figure 25, is larger than the 29 Si abundance in the M ZAMS = 20 and 30 M models but traditionally smaller in the M ZAMS = 15 and 25 M models.…”
Section: +002supporting
confidence: 90%
“…For comparison, the solar 29 Si/ 30 Si ratio, as derived by Asplund et al (2009) is 1.52, which is also consistent with the ratio derived for the ISM (Wolff 1980;Penzias 1981). Peng et al (2013) investigate the 29 Si/ 30 Si ratio for 15 evolved stars and come to the conclusion that the older low-mass oxygen-rich stars in their sample have lower 29 Si/ 30 Si ratios, but the ratios are not influenced strongly by AGB evolution and merely reflect the interstellar environment in which the star has been born. The only S-type star in their sam-ple, χ Cyg, shows a 29 Si/ 30 Si ratio of 1.1, which is incidentally identical to our derived value for W Aql.…”
Section: Siliconsupporting
confidence: 83%
“…For 28 Si/ 30 Si, also calculated from SiS, they find 16, less than half of our value of 40 ± 8. Peng et al (2013) observed the less abundant isotopologues of SiO and hence calculated the 29 Si/ 30 Si ratio for a sample of stars, including IK Tau. They found a ratio of 1.60 ± 0.30, in good agreement with our result of 1.7 ± 0.3.…”
Section: Discussionmentioning
confidence: 99%